SKOR Jaarverslag 2000. - Gould, Dan; Rombouts, Ton; Rudelius, Julika (Amsterdam : SKOR (Stichting Kunst en Openbare Ruimte), 2001)
Bade, David ; van Bentem, Hans ; Bolink, Merijn ; Colton, Adam ; Gould, Dan ; Heiden, Cécile Van Der ; Houseago, Thomas ; Jongenelis, Hewald ; Mayer Hermann, Jürgen ; Sekula, Allan ; Signer, Roman ; Sterren, Gé-Karel Van Der ; Vendel, Paul ; Vermeulen, Alex ; de Vries, Herman ; Vroegindeweij, Leo ; Weeda, Erik ; Weijers, Louwrien ; Zijlmans, Sylvie
Nederlands
boek